Analisis Kurikulum Pelajaran Alquran Hadis di Madrasah Aliyah Negeri Kota Binjai - Arlina; Rizki, Juan Adji; Sihombing, Diky Ananta; Reza, Muammar Huzaifi Haqqi; Putri, Nur Amalia; Harahap, Sandi Mahatir (Ikatan Dai Indonesia, 2023)
This study aims to describe the percentage of competency components and material analysis in the Al-Quran Hadith curriculum at the Madrasah Aliyah level. This research is a qualitative analytic narrative research using data collection using documentation and interview methods. The conclusion of this study is that the competency content in the Al-Quran Hadith curriculum in MA in the aspect of spiritual affective competence (KI-1) is at the Characterization stage (A5) by 90%, social affective competence (KI-2) is at the characterization level with percentage of 100%, cognitive competence (KI-3) is at the level of analysis (C4) using a total percentage of 97%, and psychomotor competence (KI-4) 63%. And also in this curriculum can help teachers in the learning process.